2022
DOI: 10.1111/jdi.13884
|View full text |Cite
|
Sign up to set email alerts
|

β cell replacement therapy for the cure of diabetes

Abstract: Islet transplantation is an important option in the treatment of type 1 diabetes. However, a donor shortage and immunosuppressant-related complications are the current major hurdles of islet transplantation. In this review, we discuss recent updates on islet transplantation to overcome these current obstacles and we share our perspectives on future b cell replacement therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 43 publications
(61 reference statements)
0
5
0
Order By: Relevance
“…However, there are currently two major hurdles for islet transplantation, including shortage of β‐cell source and the method to overcome the recipient's immune response. Several strategies have been investigated for these hurdles 6 . For the shortage of β‐cell source, new technologies are developing to produce β‐like cells from embryonic stem cells or induced pluripotent stem cells.…”
Section: Time After First Islet Transplantation 1 Year 5 Years 10 Yea...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are currently two major hurdles for islet transplantation, including shortage of β‐cell source and the method to overcome the recipient's immune response. Several strategies have been investigated for these hurdles 6 . For the shortage of β‐cell source, new technologies are developing to produce β‐like cells from embryonic stem cells or induced pluripotent stem cells.…”
Section: Time After First Islet Transplantation 1 Year 5 Years 10 Yea...mentioning
confidence: 99%
“…Several strategies have been investigated for these hurdles. 6 For the shortage of β‐cell source, new technologies are developing to produce β‐like cells from embryonic stem cells or induced pluripotent stem cells. However, there are still some problems to be solved before their clinical application, especially the improvement in differentiation efficiency, interpatient variability of β‐like cells' function, and long‐term graft survival and safety data.…”
mentioning
confidence: 99%
“…Harvesting functional insulin-producing cells from recently deceased donors provides a replacement strategy for beta-cells lost to autoimmune destruction. While a promising treatment option, long-term success of islet transplants could be improved, with recipients who maintain stable blood glycemia dropping from 87.5% to 71% after one year, with significant decline thereafter [1,2]. The most direct threats to successful islet transplantation are the instant blood-mediated inflammatory response (IBMIR) and hypoxia due to difficulty establishing sufficient vascular connectivity [3].…”
Section: Introductionmentioning
confidence: 99%
“…The transplantation of donor human islets can virtually cure diabetes by eliminating the need for insulin injections. In vitro differentiation of both human embryonic stem cells and induced pluripotent stem cells is being actively pursued as an islet cell replacement source 21,22 . It also has been reported that the pancreatic b-cell mass can be expanded in vivo and in vitro by MYCL-mediated reprogramming 23 .…”
mentioning
confidence: 99%
“…It also has been reported that the pancreatic b-cell mass can be expanded in vivo and in vitro by MYCL-mediated reprogramming 23 . Macro-encapsulation devices for islet cells are being developed that contain and protect the cells from immune attack 21,22 . Importantly, Timothy Kieffer and his associates 24 have reported that the implantation of pluripotent stem-cellderived pancreatic endoderm can detect meal-induced C-peptide secretion in people with type 1 diabetes.…”
mentioning
confidence: 99%